Herbicide-resistant weeds : From research and knowledge to future needs - Busi, Roberto (2013)
Fil: Vila-Aiub, Martín Miguel. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura (IFEVA). Buenos Aires, Argentina.